Avances de investigacion - seccion yuca - name - López Montes, Antonio José (International Center for Tropical Agriculture, 1990)
Results of research carried out at El Carmen Regional Research Center during 1987A/1988A are presented. The process of var. selection is carried out in 3 phases: F1C1, the 1st F1 clonal generation; preliminary yield trials; and yield trials. The selection criteria applied in each trial are detailed and the selected clones listed. Data on yield, DM accumulation, fresh wt. of commercial roots, height of branching, length of root peduncle, and HI are given for the different trials. Likewise, preliminary information is given on the 1st exptl. cycle on the 3 branching habits observed in regional var. Venezolana (late or intermediate, very late or high, no branching). (CIAT)